Effect of solid state fermentation by Enterococcus faecalis M2 on antioxidant and nutritional properties of wheat bran. (July 2020) - Mao, Menglan; Wang, Pei; Shi, Kexin; Lu, Zhaoxin; Bie, Xiaomei; Zhao, Haizhen; Zhang, Chong; Lv, Fengxia
Abstract: Wheat bran is the main by-product during wheat flour processing. Although wheat bran is rich in the bioactive compounds and antioxidant capacity, it is not widely utilized in its natural state. To improve the antioxidant and nutritional properties of wheat bran, a dominant strain, Enterococcus faecalis M2, was screened from lactic acid bacteria (LAB) isolated from various foods. Following solid state fermentation, the soluble dietary fiber content of wheat bran nearly quadrupled compared to the raw material. Total proportion of phenols, flavonoids, alkylresorcinols, along with the antioxidant capacity and free radical scavenging rate were significantly improved, particularly the ferulic acid content increased by 5.5 times. Additionally, the free amino acid content increased with degradation of wheat bran protein, whereas the level of anti-nutrient phytic acid decreased. The results of this study could provide an effective method for biological modification of wheat bran, which further enhance the health benefit and utilization of bran. Graphical abstract: Image 1 Highlights: Screening of lactic acid bacteria for improving antioxidant ability of wheat bran. Effects of solid state fermentation on physical and chemical properties of wheat bran. Solid state fermentation improved the antioxidant properties of wheat bran. Changes of active compounds of wheat bran before and after solid state fermentation.